The four facets of self-collection service for e-commerce delivery : conceptualisation and latent class analysis of user segments - Wang, Xueqin (2021)
With the rapid growth of e-commerce and technology-based self-services, consumers are increasingly encouraged to co-create individualised self-collection services. This study aims to conceptualise the multiple key facets of self-collection as viewed from consumers' perspectives and identify the latent consumer segments of the service. A total of 603 valid responses are collected, and the data are analysed using the latent class analysis. Adopting the paradigm of value co-creation, we conceptualised the self-collection service as service innovation, an empowerment tool, a green initiative and a value-based experience. Based on the conceptualisation, five latent segments of the service are identified, which are labelled as Patrons, Traditionalists, Self-enhancers, Green-lovers and Haters (from the largest to the smallest segment). By doing this, this study contributes to the literature by demonstrating the heterogeneity in consumers' participation patterns of value co-creation in e-commerce last-mile logistics.